An Elucidation of Neutrophil Functions against Mycobacterium tuberculosis Infection. (7th November 2013) - Morris, Devin; Nguyen, Thien; Kim, John; Kassissa, Christine; Khurasany, Melissa; Luong, Jennifer; Kasko, Sarah; Pandya, Shalin; Chu, Michael; Chi, Po-Ting; Ly, Judy; Lagman, Minette; et al.
Abstract : We characterized the functions of neutrophils in response to Mycobacterium tuberculosis ( M. tb ) infection, with particular reference to glutathione (GSH). We examined the effects of GSH in improving the ability of neutrophils to control intracellular M. tb infection. Our findings indicate that increasing the intracellular levels of GSH with a liposomal formulation of GSH (L-GSH) resulted in reduction in the levels of free radicals and increased acidification of M. tb containing phagosomes leading to the inhibition in the growth of M. tb . This inhibitory mechanism is dependent on the presence of TNF- α and IL-6. Our studies demonstrate a novel regulatory mechanism adapted by the neutrophils to control M. tb infection.